Diazoxide and Exercise Enhance Muscle Contraction during Obesity by Decreasing ROS Levels, Lipid Peroxidation, and Improving Glutathione Redox Status - Mariana Gómez-Barroso; Koré M. Moreno-Calderón; Elizabeth Sánchez-Duarte; Christian Cortés-Rojo; Alfredo Saavedra-Molina; Alain R. Rodríguez-Orozco; Rocío Montoya-Pérez (MDPI AG, 2020)
Obesity causes insulin resistance and hyperinsulinemia which causes skeletal muscle dysfunction resulting in a decrease in contraction force and a reduced capacity to avoid fatigue, which overall, causes an increase in oxidative stress. KATP channel openers such as diazoxide and the implementation of exercise protocols have been reported to be actively involved in protecting skeletal muscle against metabolic stress; however, the effects of diazoxide and exercise on muscle contraction and oxidative stress during obesity have not been explored. This study aimed to determine the effect of diazoxide in the contraction of skeletal muscle of obese male Wistar rats (35 mg/kg), and with an exercise protocol (five weeks) and the combination from both. Results showed that the treatment with diazoxide and exercise improved muscular contraction, showing an increase in maximum tension and total tension due to decreased ROS and lipid peroxidation levels and improved glutathione redox state. Therefore, these results suggest that diazoxide and exercise improve muscle function during obesity, possibly through its effects as KATP channel openers.